Development of open-ended HOTS questions for elementary school students' creativity - Anjar Triyono; S. Subanji; Slamet Arifin (Inovasi Kurikulum)
This study aims to develop open-ended Higher-Order Thinking Skills (HOTS) questions to assess students' conceptual abilities in plane geometry. This development was carried out to provide assessment instruments following the curriculum and encourage creative problem solving. This research uses the research and development (R and D) method with the ADDIE model, which consists of five stages: analysis, design, construction, implementation, and evaluation. The research subjects were fourth-grade students of SDN Bareng 3 Malang. The research instruments included an expert report, a student survey for question validation, and an open-ended question analysis to measure the questions' validity, reliability, difficulty level, and differentiating power. Five open-ended questions related to pictures were used in this study. The results showed that the questions developed were valid. Thus, the open-ended HOTS questions can be used as valid and reliable assessment instruments and encourage student creativity in learning plane geometry.